Solve polynomial in simplest form? 1/9m(6m-4n) Algebra Polynomials and Factoring Zero Product Principle 1 Answer Zachary M. May 16, 2017 2/3m^2-4/9mn Explanation: 1/9m(6m-4n) Distribute the 1/9m ((1/9m*6m)-(1/9m*4n)) (2/3m^2)-(4/9mn) 2/3m^2-4/9mn Answer link Related questions What is the Zero Product Principle? How to use the zero product principle to find the value of x? How do you solve the polynomial 10x^3-5x^2=0? Can you apply the zero product property in the problem (x+6)+(3x-1)=0? How do you solve the polynomial 24x^2-4x=0? How do you use the zero product property to solve (x-5)(2x+7)(3x-4)=0? How do you factor and solve b^2-\frac{5}{3b}=0? Why does the zero product property work? How do you solve (x - 12)(5x - 13) = 0? How do you solve (2u+7)(3u-1)=0? See all questions in Zero Product Principle Impact of this question 1883 views around the world You can reuse this answer Creative Commons License